PEMBERIAN ROM AKTIF TERHADAP TINGKAT KEMAMPUAN ADL DASAR PADA PASIEN POST OPERASI FRAKTUR EKSTREMITAS BAWAH DENGAN TINDAKAN ORIF DI RSUD DR. ZAINOEL ABIDIN BANDA ACEH - Taufik; Roma Sitio; Said Devi Elvin; Zakiah Reubiyana (JOURNAL KEPERAWATAN, 2022)
Based on data from the WHO, in 2013 there were 1.3 million people suffering from fractures due to traffic accidents. Fracture patients have limitations in carrying out their daily activities and active ROM exercises need to be done. The purpose of the study was to determine the effect of giving active ROM on the level of basic ADL ability in postoperative lower extremity fracture patients with ORIF action at RSUDZA Banda Aceh in 2018. The research design used in this study was Quasi Experiment with Static Group Comparison, Sampling in this study conducted by purposive sampling technique totaling 20 respondents. Data was collected using the basic ADL observation sheet. The results showed that the basic ADL ability scores in the intervention group were mostly in the mild dependency category, as much as 60%, while in the control group many were in the moderate dependency category, as much as 40%. Basic ADL in postoperative lower extremity fracture patients with ORIF action in Raudhah 6 and Raudhah 7 RSUDZA Banda Aceh (p = 0.008) which means Ha is accepted and H0 is rejected. The importance of doing active ROM for postoperative lower extremity fracture patients with ORIF action to help the healing process. It is hoped that nurses will provide an explanation of active ROM exercises as a permanent activity in an effort to prevent loss of body function abilities.